2019
DOI: 10.12669/pjms.35.2.463
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscopic minimally invasive surgery and small bone window craniotomy hematoma clearance in the treatment of hypertensive cerebral hemorrhage

Abstract: Objective: To analyze the effects of neuroendoscopic minimally invasive surgery and small bone window craniotomy hematoma clearance through comparing clinical indicators of the two operation modes and to provide a reference for selection of proper minimally invasive surgery. Methods: One hundred and twenty-six patients with hypertensive cerebral hemorrhage who received diagnosis and treatment in our hospital between December 2015 and December 2017 were selected and grouped into an observation group (n=63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Inclusion criteria for this study were: (1) confirmation of unilateral supratentorial intracerebral hemorrhage (which could be accompanied by hematoma rupture into the ventricle) by computed tomography (CT); (2) basal ganglia hemorrhage > 30 ml; (3) subcortical hemorrhage > 30 ml and midline displacement > 5 mm; and (4) surgical treatment was performed within 6-24 h of onset of spontaneous ICH. Exclusion criteria for this study were: (1) intracerebellar hemorrhage; (2) intracranial vascular malformations, aneurysms, or intracerebral hemorrhage caused by brain trauma or brain tumor in patients older than 75 years; (3) cerebral hernia requiring standard large craniotomy; (4) patients with severe systemic diseases or coagulation disorders who could not tolerate surgery; (5) patients or their families who did not agree with surgery and did not sign the informed consent; (6) bleeding > 60 ml; or (7) a GCS score ≤ 6.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Inclusion criteria for this study were: (1) confirmation of unilateral supratentorial intracerebral hemorrhage (which could be accompanied by hematoma rupture into the ventricle) by computed tomography (CT); (2) basal ganglia hemorrhage > 30 ml; (3) subcortical hemorrhage > 30 ml and midline displacement > 5 mm; and (4) surgical treatment was performed within 6-24 h of onset of spontaneous ICH. Exclusion criteria for this study were: (1) intracerebellar hemorrhage; (2) intracranial vascular malformations, aneurysms, or intracerebral hemorrhage caused by brain trauma or brain tumor in patients older than 75 years; (3) cerebral hernia requiring standard large craniotomy; (4) patients with severe systemic diseases or coagulation disorders who could not tolerate surgery; (5) patients or their families who did not agree with surgery and did not sign the informed consent; (6) bleeding > 60 ml; or (7) a GCS score ≤ 6.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…While traditional treatments are recognized, there remains a lack of consensus regarding standardized treatment (2,21,27). In recent years, an increasing number of studies have indicated that use of endoscopy to remove hematomas is less invasive and more effective (7,23).…”
mentioning
confidence: 99%
“…[ 6 ] However, intracranial surgery often requires the indwelling of various drainage tubes, and the risk of complications such as rebleeding and pulmonary infection is high. [ 7 , 8 ] Therefore, the prevention and treatment of related complications after intracranial surgery is essential.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of modern imaging technology and the introduction of stereotactic, navigation, robotic, and other procedures, minimally invasive surgery to accomplish puncture drainage is increasingly being applied in the clinical setting. However, this procedure shows no significant difference in surgical benefits compared with small bone window surgery (17).…”
Section: Discussionmentioning
confidence: 90%